Sosialisasi Peran Orang Tua di Era Digital Pada Tk 20 Junior Kota Jambi - Juwita; Siska Sartika; Grace Lestari Sitanggang; Teti Tampubolon; Sinta Wulandari; Diva Grasiella Haloho; Winda Sherly Utami; Indryani (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
The increasing use of digital technology among early childhood without adequate parental guidance has become a major issue faced by the community partner, namely parents of students at TK 20 Junior Kota Jambi. Limited parental digital literacy may lead to negative impacts on children’s social, emotional, and cognitive development. This Community Empowerment Learning (PPM) activity aimed to improve parents’ digital literacy as an effort to strengthen digital parenting practices for early childhood. The proposed solution was implemented through an interactive digital literacy socialization program using lectures, sharing sessions, and question-and-answer activities conducted in three stages: preparation, implementation, and evaluation. The results showed an improvement in parents’ understanding of the risks of unassisted gadget use, digital supervision strategies, and the importance of regulating screen time and selecting age-appropriate content. In addition to increased knowledge, the activity encouraged positive changes in parents’ attitudes and commitment to applying more structured digital parenting practices. The implications indicate that digital literacy socialization is an effective preventive approach to reducing the digital gap between parents and children and strengthening collaboration between schools and families.